P5 Learning Strategy Based on Local Wisdom to Develop Herbal Medicine Literacy and Character Profile of Pancasila Students - Wahyuni, Sri; Juharyanto, Juharyanto (Proceedings Series of Educational Studies, 2025)
Projek Penguatan Profil Pelajar Pancasila (P5) has become mandatory in implementing the Kurikulum Merdeka. This study aims to describe the P5 learning strategy, focusing on local wisdom to promote literacy in herbal medicine and foster the character of the Pancasila Student Profile. Utilizing a qualitative approach, the research includes observations and documentation. The findings indicate that implementing the P5 strategy based on local wisdom enhances the character traits of the Pancasila Student Profile such as faith and purity, critical thinking, and creativity while also developing additional competencies related to literacy in herbal medicine. The competency of literacy medicine can serve as a provision for students to preserve local wisdom in society, specifically regarding the culture of consuming herbal medicine healthily and properly to maintain a sustainable healthy life. The success of the P5 strategy, which can develop student competencies, is achieved through each of its stages: planning, implementation, assessment processing, and evaluation and follow-up. Each strategy in these four steps is interconnected.